2014
DOI: 10.1128/jb.01516-14
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Outer Membrane Protein OmpA2 in Caulobacter crescentus Depends on the Position of the Gene in the Chromosome

Abstract: The outer membrane of Gram-negative bacteria is an essential structure involved in nutrient uptake, protection against harmful substances, and cell growth. Different proteins keep the outer membrane from blebbing out by simultaneously interacting with it and with the cell wall. These proteins have been mainly studied in enterobacteria, where OmpA and the Braun and Pal lipoproteins stabilize the outer membrane. Some degree of functional redundancy exists between these proteins, since none of them is essential b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Both OmpA2 structural domains are necessary for gradient formation. In our previous work, we showed that in C. crescentus, OmpA2 forms a concentration gradient from the early stages of the cell cycle and it becomes stronger as the cell grows and ages (17). To evaluate the contribution of each of the OmpA2 structural domains to the formation of the gradient, we substituted the wild-type ompA2 allele with truncated versions that consisted of only the ␤-barrel or the C-terminal PBD of OmpA2 fused to the mCherry (mCh) fluorescent protein ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both OmpA2 structural domains are necessary for gradient formation. In our previous work, we showed that in C. crescentus, OmpA2 forms a concentration gradient from the early stages of the cell cycle and it becomes stronger as the cell grows and ages (17). To evaluate the contribution of each of the OmpA2 structural domains to the formation of the gradient, we substituted the wild-type ompA2 allele with truncated versions that consisted of only the ␤-barrel or the C-terminal PBD of OmpA2 fused to the mCherry (mCh) fluorescent protein ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, we proposed that the OmpA2 polar gradient forms before the protein is immobilized by its interaction with the cell wall or by its insertion in the OM (17). FRAP experiments showed that the full OmpA2 protein does not diffuse, and in consequence, the gradient must form before the protein is anchored.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Plasmid sequences were confirmed and the genotypes of the strains were verified by PCR and phenotype or only by phenotype when the strain was obtained from a transduction. For Western blots, SDS-PAGE-resolved proteins were transferred to nitrocellulose membranes and were incubated with a mouse polyclonal anti-red fluorescent protein (anti-RFP) antibody raised against 6ϫHis-tagged mouse RFP (65) or with a commercial anti-GFP monoclonal mouse antibody (Clontech). For detection, an alkaline phosphatase-conjugated anti-mouse antibody (Sigma) was used together with Tropix CDP-Star/Nitro-block substrate.…”
Section: Methodsmentioning
confidence: 99%